If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7-3(2x-4)=0
We simplify the equation to the form, which is simple to understand
7-3(2x-4)=0
Reorder the terms in parentheses
7+(-6x+12)=0
Remove unnecessary parentheses
+7-6x+12=0
We move all terms containing x to the left and all other terms to the right.
-6x=0-7-12
We simplify left and right side of the equation.
-6x=-19
We divide both sides of the equation by -6 to get x.
x=3.16666666667
| 46=2(4y+3)-8 | | 4t-6=24-t | | 2/3x+3=-9 | | 11x+7x+5=59 | | n+5=11k | | n+5/11 | | 13x+12=9x+24 | | 12x-8=2x+12 | | =-58 | | (1)/(t-1)+(t)/(6t-5)=(1)/(6) | | 4x+58=5y-2 | | 0=-7x^2+2x+6 | | 0=-4x^2+5x+5 | | 3p(2x+3)=15 | | x-13=4(3x-4(x-2)) | | 4=-16/j | | .8x+.05(6-x)=.10(-42) | | 0.33y-5=3 | | x+(x/4)+(x/2)=100 | | 7+8=127 | | 1/5(10j+5k) | | y=2(3)+6 | | a+7/8-a-2/3=4/3 | | 54x^2+36x+6=0 | | -10x-64=118+3x | | 11-12x=-10x-37 | | -168=8(7x+14) | | 12=i*10 | | -60=6x+3(4x+10) | | -2x-51=102-11x | | 7x-6(4x+18)=-193 | | -4x-7(-x-3)=51 |